(untitled) (American Journal of Pedagogical and Educational Research, 2023)
The article analyzes the views on truth of ancient Western philosophers such as Plato, Aristotle, Democritus, Heraclitus and Zeno, and discusses the importance of dogmatic and skeptical ideas in revealing the content and concept of truth.